Franz Boas papers - Boas, Franz, 1858-1942.
Personal and professional correspondence, diaries, and Boas (Boaz) family papers relating chiefly to Boas's career as an anthropologist and social scientist. Subjects include anthropology and linguistics in the U.S.; the development of their study; and anthropology in Latin America. Other subjects include academic freedom, race, and science.
Microfilm produced from originals in the American Philosophical Society Library.
American Philosophical Society
Anthropologist, linguist, ethnologist, educator, and curator.
Collection material in English, French, German, and Spanish.
The finding aid to the originals of this collection and other Boas material at the American Philosophical Society is available online.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Boaz family; Academic freedom; Anthropology; Anthropology -- Study and teaching; Anthropology -- Latin America; Anthropology -- United States; Linguistics; Linguistics -- Study and teaching; Linguistics -- United States; Race relations; Science; Social sciences; Anthropologists; Curators; Educators; Ethnologists; Linguists